Formulasi Sediaan Sampo Antiketombe Ekstrak Etanol Daun Jambu Air (Syzygium aqueum (Burm.f.) Alston) - Neni Sri Gunarti; Himyatul Hidayah; Bintang Larasati; Putri Agustina (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
Syzygium aqueum (Burm.f) Alston) leaves have many ingredients that are beneficial to health, one of which is as an antifungal for fungi that cause anti dandruff. To optimize this content, an anti dandruff shampoo formulation was made with the active ingredient ethanol extract of Syzygium aqueum (Burm.f) Alston leaves against Malassezia furfur. The purpose of this study was to determine the effect of extract concentration on the quality of the preparation and to find out which formula had the best antidandruff activity. The research method used was quasi experimental. The results of the phytochemical screening of the ethanol extract of Syzygium aqueum positively contained alkaloids, flavonoids, saponins, tannins, quinones and steroids. The Minimum Inhibitory Concentration showed inhibitory activity at a concentration of 1.56% using the well diffusion method. In the preparation activity test on F1; F2; and F3 with an extract concentration of 1.5%; 2% and 2.5% showed the potential as a very strong anti-dandruff category with an average inhibition zone diameter of 23.41±1.60 mm; 28.11±3.66 mm and 30.21±0.92 mm. The results of the evaluation of the physical properties of the preparation are in the form of a viscous semi-liquid, with a distinctive aromatic odor with a white to brownish green color with an average pH of 5.28±0.02 ; 6.16±0.01 ; 6.18±0.00 and 6.23 ± 0.01 with an average viscosity of 3550.3±38.88 cPs ; 3279±68.94 cPs ; 2656.6±33.29 cPs and 2568.6±108.14 cPs and foam height of 23.11±1.57 mm ; 31.76±1.95mm ; 43.03±0.77 mm and 49.06±1.37 mm, which means that the results of the physical evaluation of the preparations met the criteria. From the research that has been done, it can be seen that F3 with an extract concentration of 2.5% showed the best anti-dandruff activity.